(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objective: To evaluate the nutritional status and serum zinc concentration and some related factors of children 0-36 months. Methods: Cross-sectional description based on medical records of 245 children. Results: The rate of malnutrition wasting was 5.3%, stunting was 17.5% and underweight was 8.6%, notably the rate of overweight and obesity was 9.4% and there was a statistically significant difference between the 2 age groups with p <0.05 and OR (CI 95%) 0.3 (0.12-0.76). The rate of zinc deficiency was up to 51.4% and there was a statistically significant difference between the 2 age groups with p <0.05 and OR (CI 95%) 1.9 (1.17-3.26) and the average serum zinc concentration had a statistically significant difference between the 2 age groups with p <0.05. Children with malnutrition wasting and overweight /obesity have a significantly higher risk of zinc deficiency and there is a statistically significant difference with p<0.05. Conclusion: The rate of malnutrition and zinc deficiency is still high in children aged 0-36 months, especially stunting, overweight and obesity.